2012
DOI: 10.1128/iai.05843-11
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis-Mediated Protection from Citrobacter rodentium-Associated Enteric Disease RequiresespHand Functional Flagella

Abstract: Commensals limit disease caused by invading pathogens; however, the mechanisms and genes utilized by beneficial microbes to inhibit pathogenesis are poorly understood. The attaching and effacing mouse pathogen Citrobacter rodentium associates intimately with the intestinal epithelium, and infections result in acute colitis. C. rodentium is used to model the human pathogens enterohemorrhagic Escherichia coli and enteropathogenic E. coli. To confirm that Bacillus subtilis, a spore-forming bacterium found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…In addition, administration of the moderate-dose BLS mix increased the number of GCs in the ileum during F4 ϩ ETEC infection. Consistent with our results, B. subtilis pretreatment reduces the severity of Citrobacter rodentium-induced diarrhea in mice, partly through inhibition of GC loss in the colon (47). Furthermore, Bacteroides thetaiotaomicron increases the number of GCs and the expression of mucin genes in gnotobiotic rats, whereas Faecalibacterium prausnitzii diminishes this effect in a process involving acetate and butyrate metabolism (48).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, administration of the moderate-dose BLS mix increased the number of GCs in the ileum during F4 ϩ ETEC infection. Consistent with our results, B. subtilis pretreatment reduces the severity of Citrobacter rodentium-induced diarrhea in mice, partly through inhibition of GC loss in the colon (47). Furthermore, Bacteroides thetaiotaomicron increases the number of GCs and the expression of mucin genes in gnotobiotic rats, whereas Faecalibacterium prausnitzii diminishes this effect in a process involving acetate and butyrate metabolism (48).…”
Section: Discussionsupporting
confidence: 88%
“…B. subtilis is a gram positive spore-forming bacterium present in the gastrointestinal tract of both humans and mice (8, 9). Several groups report that select probiotic strains of B. subtilis relieve the symptoms associated with antibiotic-associated diarrhea and irritable bowel syndrome in human patients; however the mechanisms of protection have not been well established (6, 8).…”
Section: Introductionmentioning
confidence: 99%
“…To test this idea, we used biofilm mutants, predicting that these mutants would not prevent C. rodentium-induced disease. Surprisingly, some biofilm mutants were protective and others were not, even though all of the mutants tested were present at levels comparable to wild type [32] . All protective strains were capable of producing EPS as part of their biofilm matrix, leading us to suggest that EPS is the protective molecule of B. subtilis.…”
Section: Immunomodulation By Bacillus Subtilis Eps: Macrophagesmentioning
confidence: 93%
“…Our lab has studied the beneficial role of the intestinal microbiota for years and recently, we showed that a single dose of B. subtilis prevents enteric inflammatory disease in mice infected with Citrobacter rodentium [32] . C. rodentium is an attaching and effacing murine pathogen that associates intimately with the epithelium to induce colitis in a manner similar to the human pathogen, enteropathogenic E. coli [33,34] .…”
Section: Immunomodulation By Bacillus Subtilis Eps: Macrophagesmentioning
confidence: 99%